Acute effects of countermovement jumping and sprinting on shot put performance - Terzis, G.; Karampatsos, G.; Giorgos, K.; Thomas, K. (The Journal of Strength and Conditioning Research, 2012)
The purpose of this study was to investigate the acute effects of countermovement jumping and sprinting on shot put performance in experienced shot putters. Ten shot putters (best performance 13.16-20.36 m) participated in the study. After a standard warm-up including jogging, stretching, and 4-6 submaximal puts, they performed 3 shot put attempts with maximum effort, separated with 1.5-minute interval. Three minutes later, they performed 3 maximal consecutive countermovement jumps (CMJs). Immediately after jumping, they performed 3 shot put attempts with maximum effort, separated with a 1.5-minute interval. One week later, they carried out a similar protocol, at similar external conditions, but they performed a bout of 20-m sprinting instead of the CMJs, to potentiate shot put performance. Muscular strength (1 repetition maximum in squat, snatch, bench press, incline bench press) and body composition (dual x-ray absorptiometry) were measured during the same training period (±10 days from the jumping and sprinting protocols). Shot put performance was significantly increased after the CMJs (15.45 ± 2.36 vs. 15.85 ± 2.41 m, p = 0.0003). Similarly, shot put performance was significantly increased after sprinting (15.34 ± 2.41 vs. 15.90 ± 2.46 m, p = 0.0007). The increase in performance after sprinting was significantly higher compared with the increase after jumping (2.64 ± 1.59 vs. 3.74 ± 1.88%, p = 0.02). In conclusion, the results of this study indicate that a standard warm-up protocol followed by 3 maximal bouts of shot put and either 3 consecutive countermovement jumps or a bout of 20-m sprinting induce an acute increase in shot put performance in experienced shot putters.